Dispersion of the Nabro volcanic plume and its relation to the Asian summer monsoon - T. D. Fairlie; J.-P. Vernier; M. Natarajan; K. M. Bedka (Atmospheric Chemistry and Physics, 2014)
We use nighttime measurements from the Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite, together with a Lagrangian trajectory model, to study the initial dispersion of volcanic aerosol from the eruption of Mt. Nabro (Ethiopia/Eritrea) in June 2011. The Nabro eruption reached the upper troposphere and lower stratosphere (UTLS) directly, and the plume was initially entrained by the flow surrounding the Asian anticyclone, which prevails in the UTLS from the Mediterranean Sea to East Asia during boreal summer. CALIPSO detected aerosol layers, with optical properties consistent with sulfate, in the lower stratosphere above the monsoon convective region in South and Southeast Asia within 10 days of the eruption. We show that quasi-isentropic differential advection in the vertically sheared flow surrounding the Asian anticyclone explains many of these stratospheric aerosol layers. We use Meteosat-7 data to examine the possible role of deep convection in the Asian monsoon in transporting volcanic material to the lower stratosphere during this time, but find no evidence that convection played a direct role, in contrast with claims made in earlier studies. On longer timescales, we use CALIPSO data to illustrate diabatic ascent of the Nabro aerosol in the lower stratosphere at rates of ~ 10 K per month for the first two months after the eruption, falling to ~ 3 K per month after the Asian anticyclone dissipates. Maps of stratospheric aerosol optical depth (AOD) show local peaks of ~ 0.04–0.06 in July in the region of the Asian anticyclone; we find associated estimates of radiative forcing small, ~ 5–10% of those reported for the eruption of Mt. Pinatubo in 1991. Additionally, we find no clear response in outgoing shortwave (SW) flux due to the presence of Nabro aerosol viewed in the context of SW flux variability as measured by CERES (Clouds and Earth Radiant Energy System).